PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA KARYAWAN DENGAN QUALITY OF WORK LIFE SEBAGAI VARIABEL MEDIASI PADA INDUSTRI PERBANKAN DI WAY JEPARA LAMPUNG TIMUR - Yolla Zelika Desastra (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2022)
The application of the transformational leadership style of the banking industry in Way Jepara, East Lampung, is currently ideal. Through this leadership style, all the positive values of the potential of banking organizations in Way Jepara, East Lampung can be transformed into actual frameworks to achieve company goals in an effort to face increasingly fierce business competition. In addition, the existence of a good quality of work life also fosters satisfaction for employees so that it can increase the desire of employees to stay and survive in the organization and try to provide the best for the company. This study aims to analyze the role of mediating quality of worklife in the influence of transformational leadership on job satisfaction. The data in this study were obtained from 200 employees of banking institutions in Way Jepara, East Lampung and the data were analyzed using structural equation modeling analysis. The conclusion of this study is that transformational leadership can significantly influence job satisfaction through quality of worklife. The implication of this research is that the banking institutions in Way Jepara, East Lampung must be able to provide leadership training for the management level staff so that the level management staff can become leaders who can give confidence to employees that the company's goals will be achieved, gain respect from employees, able to encourage employees to use creativity in completing work, eager to listen to new ideas or ideas, and be able to solve problems from various perspectives and try to improve self-development of employees and review existing salary systems then make revisions to existing salary systems can make employees more satisfied with paying salaries that are worth the work,